Decadal changes in species composition of rare oak Quercus chungii forests with logging history - Li, Wenbin; Zhong, Xueer; Li, Zhenji; Huang, Yonghui; Chen, Xinfeng; Huang, Lihan; Wang, Ya; Chen, Yuxin (Frontiers in Ecology and Evolution, 2024)
Quercus chungii is a tree species endemic to subtropical areas of China, rare and endangered in Fujian Province. Minqing Huangchulin National Nature Reserve was specifically established to preserve Q. chungii forests with severe logging history. How the composition of Q. chungii communities changed after the initiation of this conservation practice remains unknown. Understanding the successional trajectories of Q. chungii communities is crucial for conserving and restoring Q. chungii forests and similar secondary forests with logging history in subtropical areas. In this study, we assessed how species and phylogenetic composition of Q. chungii communities changed, and whether these temporal trajectories were primarily contributed by stochastic processes. We established two sites composed by Q. chungii adult trees in the nature reserve in 2013, and measured their species composition in 2013 and 2023, respectively. We found that the communities undergone significant species replacement and reordering from 2013 to 2023, thus leading to high temporal β diversity. These temporal changes in community composition were primarily the results of deterministic ecological processes based on the results of null model analyses. A larger contribution from nestedness than turnover to the temporal β diversity suggested that the change in species richness caused by the loss or gain of species was more important than species turnover in driving the compositional change. A larger contribution from balanced abundance variations than abundance gradient to the temporal β diversity suggested that there was no significant consistent increase or decrease in species abundance during this decade. The target species Q. chungii significantly increased in abundance and basal area, making this species rank among one of the most dominant species in the communities after a decade, indicating the effectiveness of the nature reserve in conserving Q. chungii communities. However, the over-reliance on resprouts may reduce the genetic diversity and increase the risks from natural enemies, thus limiting the future development of Q. chungii. We conclude that although Q. chungii communities undergone rapid recovery from logging disturbance, continuing efforts in studying its population structures and dynamics and their driving factors are crucial for restoring and conserving Q. chungii communities.